PENGARUH LATIHAN POWER LENGAN TERHADAP KEMAMPUAN SERVIS ATAS DAN SMASH DALAM PERMAINAN BOLA VOLI PADA UKM IKIP MATARAM TAHUN 2017 - Mujriah, Mujriah (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2017)
The problems occured in Club Players of UKM IKIP Mataram 2017 was the lack of reflexes between the power and speed when hitting the ball in the overhead serve or smash. One of efforts to improve the ability to overhead serve or smash is by arm power exercise in the form of medicine ball. This study aims to determine 1). Is there arms power exercise influence toward the ability to serve in volleyball at Club Players of UKM IKIP Mataram 2017? 2). Is there arms power exercise influence toward the ability to smash in volleyball at UKM IKIP Mataram 2017? This research used experimental methods and performance tests in the ability of the overhead serve, smash test and documentation. The samples in this research were volleyball player of Club Players of UKM IKIP Mataram 2017 Â with the total of 12 players using population studies. From the t-test results, it was obtained the t-score of overhead serve on 4.036 and t-score of smash on 3.432, while the t-able was 2.201 at significance level of 5%, so the t-score of overhead serve was higher than t-table (4.036> 2.201) that meant that the result of overhead serve was significant. While the t-score of smash was also higher than t-table which was 3.432 > 2.201. From the significant results, it can be concluded that 1). There was arms power exercise influence toward the ability to serve in volleyball at Club Players of UKM IKIP Mataram 2017. 2). There was arms power exercise influence toward the ability to smash in volleyball at Club Players of UKM IKIP Mataram 2017